Supply Chain Information Operational Model for Sugarcane Production for the Factory in Thailand - Artaphon Chansamut (ExcelingTech, 2023)
The research aimed to develop and to assess supply chain information operational model for sugarcane production for the factory in Thailand A samples are ten experts in the field of information. and supply chain. The data is analysed by means and standardized deviations. The research about supply chain information operational model for sugarcane production for the factory in Thailand consists of seven elements namely main components Suppliers , Factory (Manufacture) Distribution, Wholesaler, Consumers . The assessment about supply chain information operational model for sugarcane production for the factory in Thailand using Black- Box technique. The research findings revealed that supply chain information operational model for sugarcane production for the factory in Thailand is appropriate at the high level and can be develop information system.